Perbedaan Inhalasi Essential Oil Lemon dan Oral Lemon terhadap Penurunan Frekuensi Mual Muntah pada Ibu Hamil Trimester Pertama - Lilik Setiyowati; Agnes Isti Harjanti; Dany Putri S (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Nausea and vomiting (morning sickness), experienced by around 70–80% of pregnant women, is a phenomenon that often occurs at 5–12 weeks of gestation. Lemon is one of the herbal oils that is a safe medicine against morning sickness in pregnant women. The population of this study was composed of first-trimester pregnant women with nausea and vomiting. Prior to the intervention in the oral lemon control group, there were seven respondents (28.0%) with a frequency of nausea and vomiting > 4, then 12 respondents (48.0%) with a frequency of <4 and no nausea, as well as six respondents (24.0%). After intervention in the oral lemon control group, there were five respondents (20.0%) with a frequency of nausea and vomiting > 4, then 14 respondents (56.0%) with a frequency of <4 and no nausea, and as many as six respondents (24.0%). Before the intervention, a p-value <0.001 was obtained in the control group. In the group, after being given the intervention, the p-value was <0.001. Whereas in the oral lemon control group, the p-value was <0.001 before the intervention, and after being given the oral lemon intervention, the p-value was <0.001. The research was conducted in the Ananda Clinic Work Area, Semarang Regency. The results of the study showed that there was an effect of giving lemon aromatherapy inhalation on morning sickness in pregnant women.